2008
DOI: 10.1007/s11661-008-9696-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Wear Behavior of Al-7Si-TiB2 In-Situ Composites

Abstract: In this article, the effect of temperature and load on the dry sliding wear behavior of an Al-7Si alloy reinforced with in-situ TiB 2 particles is reported. The coefficient of friction and wear rate of Al-7Si alloy and in-situ composites were measured using a high-temperature pin-on-disc apparatus. The wear tests were performed in the temperature range of 100°C to 300°C, at an applied load of 40 to 120 N. With increasing temperature, the wear rate of Al-7Si alloy increased drastically and it decreased with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 23 publications
2
25
0
1
Order By: Relevance
“…Further details on the synthesis of these in-situ composites are available in the earlier report by the present authors. [20][21][22][23][24][25] The in-situ composites prepared in these experiments are A356-5 wt pct TiB 2 , Al-4 wt pct Cu-5 wt pct TiB 2 , and A356-5 wt pct TiC. The reinforcement amount of 5 wt pct was chosen to have a lower viscosity of the melt, so that it can easily flow into the centrifugal mold.…”
Section: A Synthesis Of In-situ Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further details on the synthesis of these in-situ composites are available in the earlier report by the present authors. [20][21][22][23][24][25] The in-situ composites prepared in these experiments are A356-5 wt pct TiB 2 , Al-4 wt pct Cu-5 wt pct TiB 2 , and A356-5 wt pct TiC. The reinforcement amount of 5 wt pct was chosen to have a lower viscosity of the melt, so that it can easily flow into the centrifugal mold.…”
Section: A Synthesis Of In-situ Compositesmentioning
confidence: 99%
“…In recent years, considerable research has been done on Al-TiB 2 and Al-TiC in-situ composites (synthesized through salt reaction method), and these have shown significantly improved mechancial and tribological properties in comparison to the ex-situ composites. [20][21][22][23][24][25] However, there are no reports on the FG Al-TiB 2 and Al-TiC in-situ composites by horizontal centrifugal casting to date. In the present work, the FG Al alloy matrix in-situ composites (FG-AMCs) were produced through the centrifugal solid particle method.…”
Section: Introductionmentioning
confidence: 99%
“…And they have found that the composites have the higher percentage of contribution 63.84% influencing the wear rate of the Al 2618 composites and it is followed by Sliding Distance 20.2% and Temperature 5.32%, Load 4.01%, and Velocity 3.96%. Literature [17] has studied the high temperature wear properties of an in situ AMCs TiB 2 /Al-7Si and found that the transition of wear mode from mild to severe wear is increased to the higher loads and temperatures. Kumar et al [18] have reported that the Al-4Cu alloy showed a transition from mild to severe wear at a load of 80 N and a sliding temperature of 373 K. But with the addition of 5 and 10 wt.% of in situ TiB 2 particles to the Al-4Cu matrix, the transition temperatures are increased to 473 and 573 K and the loads are increased to 100 and 120 N, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the in situ composites have significant advantages, some synthesis routes may lead to composite with inhomogeneous microstructure with various unstable and/or undesirable phases. S.Kumar et al [5] have investigated the Effect of temperature on the wear behaviour of Al-7Si-TiB2 in-situ composites increasing temperature the wear rate of Al-7Si alloy increased drastically and decreased with the weight percent of TiB2 particles. B.S.Murty et al [6] Tensile and Wear behaviour of in-situ Al-7Si-TiB2 particulate composites.…”
Section: Introductionmentioning
confidence: 99%